Managing urban safety and security in Germany: Institutional responsibility and individual competence. (May 2013) - Frevel, Bernhard
After a short description of the broad field of urban security problems in Germany and a concentration on aspects of crime and disorder, the main institutions responsible for taking action on these problems – the police, local authorities and social services – are discussed. The institutional responsibilities are differentiated in terms of their statutory duties, and the individual competences for undertaking managerial responsibilities in this field are analysed against the background of the higher education system for training in public services in Germany. The need for collaboration in Crime Prevention Councils and Public Order Partnerships will be sketched out. The skills that already exist and those that are additionally needed for managing urban security are discussed along with the appropriate role of higher education in equipping managers with these skills.